2012
DOI: 10.1111/j.1365-2109.2012.03138.x
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary study on effects of methionine hydroxy analog and taurine supplementation in a soy protein concentrate-based diet on the biological performance and amino acid composition of rainbow trout [Oncorhynchus mykiss(Walbaum)]

Abstract: Preliminary study on effects of methionine hydroxy analog and taurine supplementation in a soy protein concentrate-based diet on the biological performance and amino acid composition of rainbow trout [Oncorhynchus mykiss (Walbaum)] Abstract A feeding trial was conducted on the effects of methionine hydroxy analog (MHA) and taurine supplementation in diets with high levels of soy protein concentrate (SPC) on the growth performance and amino acid composition of rainbow trout, Oncorhynchus mykiss (Walbaum) compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 23 publications
2
43
1
Order By: Relevance
“…Boonyoung et al. () and Mambrini et al. (), however, found no significant effects of dietary methionine on whole‐body fat content in Oncorhynchus mykiss .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Boonyoung et al. () and Mambrini et al. (), however, found no significant effects of dietary methionine on whole‐body fat content in Oncorhynchus mykiss .…”
Section: Discussionmentioning
confidence: 96%
“…However, soybean meal is deficient in methionine and particularly taurine, two sulphur‐containing amino acids. Generally, soybean‐based fish feeds are supplemented with methionine, to support optimum fish growth (Boonyoung, Haga, & Satoh, ; Espe, Hevrøy, Liaset, Lemme, & El‐Mowafi, ; Mambrini, Roem, Carvedi, Lalles, & Kaushik, ), but taurine supplementation to plant‐based feeds gained attention recently (Gaylord, Teague, & Barrows, ; Jirsa, Davis, Salze, Rhodes, & Drawbridge, ; Johnson et al., ; López, Flores‐Ibarra, Bañuelos‐Vargas, Galaviz, & True, ; Lunger, McLean, Gaylord, Kuhn, & Craig, ; Takagi et al., ; Wu, Han, Qin, & Wang, ). Taurine (2‐aminoethanesulphonic acid) is an amino acid, which does not participate in protein structure and is generated as final product of sulphur‐containing amino acids metabolism (Salze & Davis, ).…”
Section: Introductionmentioning
confidence: 99%
“…This study showed that dietary taurine did not significantly influence the growth of sea cucumbers under the present experimental conditions. The effects of taurine on growth performance of different aquatic animals including fishes (Kim et al , , ; Matsunari et al , ; Lunger et al ; Takagi et al ; Qi et al ; Salze et al ; Boonyoung et al ; Jirsa et al ) and shrimps (Shiau and Chou ; Yue et al ; Zhou et al ) were varied. It is hard to compare the effect of taurine on the growth of sea cucumbers with its effect on the growth of different fishes and shrimps.…”
Section: Discussionmentioning
confidence: 99%
“…Taurine inclusion in plant-based diets has been shown to improve the performance of several marine fish species (Lunger et al, 2007;Chatzifotis et al, 2008;Takagi et al, 2008Takagi et al, , 2010Enteria et al, 2011). In contrast, in freshwater species a taurine requirement has been observed only in rainbow trout fed FM-free diets (Gaylord et al, 2006, though such taurine requirement is still controversial (Boonyoung et al, 2013). In some marine species the estimated taurine requirement is considerably high (Goto et al, 2001;Kim et al, 2005;Qi et al, 2012;Lim et al, 2013) and this may help explain why a taurine requirement has been established essentially in marine fish, even when fed FM-containing diets.…”
Section: Fishmeal Sparing In Aquafeedsmentioning
confidence: 99%